Effects of Mg on diamond growth and properties in Fe–C system under high pressure and high temperature condition - 黄国锋 郑友进 李战厂 高强 马卓 史思明 姜宝钢 赵赫 (Chinese physics B, 2016)
Diamond crystal crystallized in Fe–Mg–C system with Archimedes buoyancy as a driving force is established under high pressure and high temperature conditions. The experimental results indicate that the addition of the Mg element results in the nitrogen concentration increasing from 87 ppm to 271 ppm in the diamond structure. The occurrence of the {100}plane reveals that the surface character is remarkably changed due to the addition of Mg. Micro-Raman spectra indicate that the half width of full maximum is in a range of 3.01 cm^-1–3.26 cm^-1, implying an extremely good quality of diamond specimens in crystallization.